Intellectual Property in Agricultural Biotechnology: Issues for Developing Countries - Crespi, Stephen (International Service for National Agricultural Research, 2001)
Intellectual property rights are rights granted by State authority for certain products of intellectual effort and ingenuity. In the technological field, intellectual property may be seen as a recognition by the State of the contribution of the innovator to the development of new or improved products and industrial technology. These rights are the subject of specific laws (statutes) enacted by Parliaments or other State Authority. Patents relate to inventions, designs relate to shapes and configurations, trade marks relate to words or symbols applied to products or services, plant varieties have their own special form of right, and copyright relates to works of literary or artistic craftsmanship. Apart from copyright, all other rights must be applied for to the relevant national authority, according to statutory law and procedure. In agricultural biotechnology, the types of right of most interest are patents and plant variety rights. To patent an invention (new product or process), it must be seen to be new, inventive and to have an industrial or other practical use. The application is officially and critically examined to see that it meets these requirements. To obtain a plant breeder's right for a new variety, it must be distinct from known varieties, uniform and stable (DUS). The variety is officially tested for these requirements.